METHODOLOGICAL APPROACHES FOR DETERMINATION AND ASSESSING THE RESOURCE POTENTIAL OF CRITICAL RAW MATERIALS IN UKRAINE - LYTVYNIUK, Stanislav; BARIATSKA, Natalia (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Industrial and technological interest in critical (strategic) mineral raw materials, given their natural scarcity, is of key importance in the global economy. A country's (or region's) supply of raw materials is a factor of economic security, autonomy and an insurance against global crises. Global and regional analytical researches on the mineral resource assessment in the context of circular and resource efficient (low-carbon) economy development have revealed a number of problematic issues related to different methodological approaches to the assessment, classification, accounting and management of critical mineral raw materials (CRM). The standardization of such approaches for economically related regions is the way to create reliable critical mineral raw material supply chains and ensure sustainable economic development.  In order to complete the outlined tasks, a wide range of studies has been used, including general scientific and special methods of scientific and applied research. In addition to general theoretical methods of analysis, statistics and systematization, a complex of methods of geological and technical-economic study of mineral raw materials has been used to achieve the set goal and complete specified tasks. Authors have attempted to define the concept of critical mineral raw materials by using basic criteria and methodical approaches of the United Nations Framework Classification (UNFC). Various classification systems used for the assessment and management of critical mineral raw materials have been considered. Practical experience of the UNFC application during the assessment of CRM resource potential in Ukraine (excluding hydrocarbons and groundwater) based on the list of the European Union has been presented. Considering the current state of the mineral raw material resource base of Ukraine, authors have suggested methodological tools for bringing the State Balance into compliance with the integrated systematic accounting in accordance with the UNFC. The analysis of the State Balance of Ukraine using the UNFC approaches has revealed primary prospects for the mineral and raw material base development, which are related to potential and perspective projects on 22 elements from the EU list of critical mineral raw materials. Ukraine possesses all the prerequisites to participate in European Union programs designed to create sustainable models of supply chains for various resources for the transition to closed-cycle zero waste consumption.
Keywords: critical raw materials; mineral resource management; categories; classification principles; United Nations Framework Classification (UNFC); United Nations Resource Management System (UNRMS)